Transportability of non-target arthropod field data for the use in environmental risk assessment of genetically modified maize in Northern Mexico - Corrales Madrid, José Luis; Martínez Carrillo, José Luis; Osuna Martínez, M. B.; Durán Pompa, Héctor Abel; Alonso Escobedo, José; Javier Quiñones, F.; Garzón Tiznado, José Antonio; Castro Espinoza, Luciano; Zavala García, Francisco; Espinoza Banda, Armando; González García, Juvencio; Jiang, C.; et al. (Blackwell Wissenschafts-Verlag, 2018)
In country, non-target arthropod (NTA) field evaluations are required to comply with the regulatory process for cultivation of genetically modified (GM) maize in Mexico. Two sets of field trials, Experimental Phase and Pilot Phase, were conducted to identify any potential harm of insect-protected and glyphosate-tolerant maize (MON89Ø34-3 × MON-88Ø17-3 and MON-89Ø34-3 × MON-ØØ6Ø3-6) and glyphosatetolerant maize (MON-ØØ6Ø3-6) to local NTAs compared to conventional maize. NTA abundance data were collected at 32 sites, providing high geographic and environmental diversity within maize production areas from four ecological regions (ecoregions) in northern Mexico. The most abundant herbivorous taxa collected included field crickets, corn flea beetles, rootworm beetles, cornsilk flies, aphids, leafhoppers, plant bugs and thrips while the most abundant beneficial taxa captured were soil mites, spiders, predatory ground beetles, rove beetles, springtails (Collembola), predatory earwigs, ladybird beetles, syrphid flies, tachinid flies, minute pirate bugs, parasitic wasps and lacewings. Across the taxa analysed, no statistically significant differences in abundance were detected between GM maize and the conventional maize control for 69 of the 74 comparisons (93.2%) indicating thatthe single or stacked insect-protected and herbicide-tolerant GM traits generally exert no marked adverse effects on the arthropod populations compared with conventional maize. The distribution of taxa observed in this study provides evidence that irrespective of variations in overall biodiversity of a given ecoregion, important herbivore, predatory and parasitic arthropod taxa within the commercial maize agroecosystem are highly similar indicating that relevant data generated in one ecoregion can be transportable for the risk assessment of the same or similar GM crop in another ecoregion.